ASPECTS OF RESPONSE TO INCIDENTS ARE CAUSED BY ANOMALIES IN THE FUNCTIONING AND MAINTENANCE OF COMPUTER SYSTEMS - MALINOVSKYI, RUSLAN; BODNARUK, VASYL (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Digital services in modern computer systems are a key element for ensuring efficient and reliable functioning of various applications. The increase in the amount of data and the complexity of software solutions makes the task of monitoring and managing functional anomalies of such services in distributed systems urgent. In this way, consideration of issues of distribution of digital services, in particular their optimization based on monitoring of functional anomalies, which can allow the development and improvement of anomaly detection methods, strategies for the distribution of computing resources, and response to detected anomalies in distributed computer systems. Taking into account the constant growth of data volumes and the complexity of the interaction of services in a distributed environment, there is a need to conduct research on large-scale distributed systems, focusing on joint activities and anomaly management. In the course of which it is advisable to pay attention to the aspects of time, coherence, coordination and computing costs for the mentioned processes. An important focus is the area of ​​critical digital infrastructure, which examines changes in software development, the transition to cloud computing, and incident response strategies, including analysis of data sources, their availability, and investigation of incident response patterns. In addition, it is necessary to pay attention to adaptive choreography, where the results of preparatory studies, elements of choreography and dynamics of coordination in incident management are considered.